A critical evaluation of resonant and dissonant leadership and their implications during the COVID-19 pandemic situation in Sri lanka - Poongothai, S.; Noorul Safna, M.I. (University of Jaffna, 2020)
There are various leadership styles practised by managers in different organizations in different situations. Leaders can develop multiple mechanisms to mitigate cognitive and behavioural risks and prevent future issues effectively. This research study investigates the resonant and dissonant leadership styles applied by managers in selected Sri Lankan public and private sector organizations during the COVID-19 pandemic situation, the consequences of applying each style and the implications. Reviewing the existing relevant literature using a mixed-method approach associated with secondary data and the personal interviews and participants’ observation have been incorporated and 30 respondents in each sector were selected based on the purposive sampling method to derive the findings. Results revealed that resonant leadership style has dominance in the public sector organizations conversely, the dissonant leadership style exerts considerable influence on private sector organizations during the COVID-19 pandemic situation in Sri Lanka. Researchers believe that since it is a life-threatening problem faced by the people globally, the role of emotional intelligence among the managers also plays a vital role. Finally, it is recommended that the hybrid leadership associated with high resonant and low dissonant is appropriate and much effective for the Sri Lankan organizations during this situation for their successful survival.
Keywords: COVID-19 pandemic; Dissonant leadership; Emotional intelligence and resonant leadership